ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DAN TINGKAT UPAH RIIL DI INDONESIA TAHUN 1992--2010 (PENDEKATAN SIMULTANEOUS REGRESSION) - Dewi Kusumawati, Ni Luh Putu (PIRAMIDA, 2012)
The aim of this research was to know the effect of real wages rates, gross domestic product, physical investment, and price changes both simultaneously or partially toward the labor absorption and also to know the effect of labor absorption, minimum wages, and education level both simultaneously or partially toward the level of real wages in Indonesia. The result showed that the variables of labor absorption, minimum wages, and education level simultaneously affected the rates of real wages in Indonesia significantly. The variables of labor absorption and minimum wages partially found affected the real wages rates positively and significantly, whilst the variable of education level partially affected the real wages rates in Indonesia negatively and significantly. On the structural equation of labor absorption, variable of real wages rates, GDP, physical investment, and price changes simultaneously affected significantly the labor absorption in Indonesia. The variables of real wage rates, GDP, and price changes partially found affected the labor absorption positively and significantly whereas the variable of physical investment partially had no effect toward the labor absorption in Indonesia.
Keywords: labor absorption; real wages rate; minimum wage